Hannah Arendt and the challenge of modernity : a phenomenology of human rights - Parekh, Serena 1974- (Studies in philosophy, 2008)
Introduction: The groundlessness of modernity -- The paradox of human rights -- Human dignity and the ethos of modernity -- The common world -- Two realms of existence -- The foundations of human rights -- Conscience, morality, and judgment